Accessibility and implementation in UK services of an effective depression relapse prevention programme - mindfulness-based cognitive therapy (MBCT): ASPIRE study protocol. - Rycroft-Malone, J; Anderson, R; Crane, R; Gibson, A; Gradinger, F; Owen Griffiths, H; Mercer, S; Kuyken, W (BioMed Central, 2014)
BACKGROUND: Mindfulness-based cognitive therapy (MBCT) is a cost-effective psychosocial prevention programme that helps people with recurrent depression stay well in the long term. It was singled out in the 2009 National Institute for Health and Clinical Excellence (NICE) Depression Guideline as a key priority for implementation. Despite good evidence and guideline recommendations, its roll-out and accessibility across the UK appears to be limited and inequitably distributed. The study aims to describe the current state of MBCT accessibility and implementation across the UK, develop an explanatory framework of what is hindering and facilitating its progress in different areas, and develop an Implementation Plan and related resources to promote better and more equitable availability and use of MBCT within the UK National Health Service. METHODS/DESIGN: This project is a two-phase qualitative, exploratory and explanatory research study, using an interview survey and in-depth case studies theoretically underpinned by the Promoting Action on Implementation in Health Services (PARIHS) framework. Interviews will be conducted with stakeholders involved in commissioning, managing and implementing MBCT services in each of the four UK countries, and will include areas where MBCT services are being implemented successfully and where implementation is not working well. In-depth case studies will be undertaken on a range of MBCT services to develop a detailed understanding of the barriers and facilitators to implementation. Guided by the study's conceptual framework, data will be synthesized across Phase 1 and Phase 2 to develop a fit for purpose implementation plan. DISCUSSION: Promoting the uptake of evidence-based treatments into routine practice and understanding what influences these processes has the potential to support the adoption and spread of nationally recommended interventions like MBCT. This study could inform a larger scale implementation trial and feed into future implementation of MBCT with other long-term conditions and associated co-morbidities. It could also inform the implementation of interventions that are acceptable and effective, but are not widely accessible or implemented.